2001
DOI: 10.1016/s0960-9822(01)00327-x
|View full text |Cite
|
Sign up to set email alerts
|

Noninformative vision improves the spatial resolution of touch in humans

Abstract: Research on sensory perception now often considers more than one sense at a time. This approach reflects real-world situations, such as when a visible object touches us. Indeed, vision and touch show great interdependence: the sight of a body part can reduce tactile target detection times [1], visual and tactile attentional systems are spatially linked [2], and the texture of surfaces that are actively touched with the fingertips is perceived using both vision and touch [3]. However, these previous findings mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
262
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(291 citation statements)
references
References 22 publications
19
262
10
Order By: Relevance
“…In line with previous studies (Kennett et al, 2001;de Vignemont et al, 2005) we expected illusory stretching and shrinking to have different effects on tactile perception. Instead, our findings suggested that both stretching and shrinking the finger significantly improved tactile perception compared to a veridical baseline condition.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with previous studies (Kennett et al, 2001;de Vignemont et al, 2005) we expected illusory stretching and shrinking to have different effects on tactile perception. Instead, our findings suggested that both stretching and shrinking the finger significantly improved tactile perception compared to a veridical baseline condition.…”
Section: Discussionsupporting
confidence: 91%
“…Given that previous studies have reported increased tactile acuity following visual enlargement and illusory elongation of a body part (Kennett et al, 2001;de Vignemont et al, 2005) we predicted that correct tactile detections would increase significantly (as a result of increased sensitivity) when the finger appeared to be stretched, compared to the veridical-baseline condition. Shrinking the finger was expected to result in one of two out comes; either no difference in tactile perception between the baseline and shrunken finger conditions (de Vignemont et al, 2005), or a significant reduction compared to baseline (Kennett et al, 2001). The detached condition was included to examine how observing body discontinuity would affect tactile perception.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This can be vision of the body itself (Kennett et al 2001) or visual stimuli presented close to the body. For example, in the crossmodal congruency task developed by Spence et al visual stimuli presented close to the body can inXuence judgements about tactile stimuli presented at the same time (for a review, see Maravita et al 2003).…”
Section: Needing a Body Of Knowledgementioning
confidence: 99%